Description of Cholinesterase Levels and Hemoglobin Levels in Male Farmers Using Organophosphate Pesticide - Purwati Purwati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Abstract Background: Pesticides can enter the body through inhalation, so it is necessary to check Cholinesterase levels to find out poisoning or exposure to pesticides in the body. Conditions of oxidative stress due to pesticides can trigger the process of lipid peroxidation in the cell membrane of erythrocytes. This process causes a loss of membrane fluidity and increased fragility or fragility of the erythrocyte membrane. Erythrocytes will easily break or lyse which will eventually cause a decrease in hemoglobin levels in the blood. Objectives : The purpose of this study was to determine Cholinesterase levels and Hemoglobin levels in male farmers using Organophosphate pesticides Research Metodes: This research method is descriptive with a cross-sectional study design.. Results: The results showed that 18 respondents (90%) had Hemoglobin levels within normal limits, the highest Hemoglobin result was 18.1 g/dL and the lowest Hemoglobin result was 11.6 g/dL. 20 respondents with a percentage of 100% had cholinesterase levels within normal limits, the highest cholinesterase result was 12485 u/L and the lowest cholinesterase result was 6985 u/L. Pearson Product Moment test results obtained a p value of 0.470 (> 0.05). Conclusion: The conclusion of this study is that there is no significant relationship between Cholinesterase levels and hemoglobin levels.